2019
DOI: 10.1038/s41598-019-54259-y
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Porphyromonas gingivalis W83 exposure leads to release pro-inflammatory cytokynes and angiotensin II in coronary artery endothelial cells

Abstract: The role of Porphyromonas gingivalis (P. gingivalis) or its virulence factors, including lipopolysaccharide (LPS) not only has been related with periodontitis but also with endothelial dysfunction, a key mechanism involved in the genesis of atherosclerosis and hypertension that involving systemic inflammatory markers as angiotensin II (Ang II) and cytokines. This study compares the effect of repeated and unique exposures of P. gingivalis W83 LPS and live bacteria on the production and expression of inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
1
20
0
1
Order By: Relevance
“…P. gingivalis has been reported to affect these processes and thereby promote hypertension. It was shown that repeated exposure of live P. gingivalis or bacteria LPS induced the release of pro-inflammatory CKs and angiotensin II in human coronary artery endothelial cells, together with P. gingivalis -associated mediators of systemic inflammation (such as CRP, IL-6, TNF-α), contributing to both endothelial dysfunction and the development of arterial hypertension [ 61 ]. Recently, an animal study supported the hypothesis that the Th1 immune response induced by P. gingivalis antigens is response for elevated BP [ 60 ].…”
Section: Cardiologymentioning
confidence: 99%
“…P. gingivalis has been reported to affect these processes and thereby promote hypertension. It was shown that repeated exposure of live P. gingivalis or bacteria LPS induced the release of pro-inflammatory CKs and angiotensin II in human coronary artery endothelial cells, together with P. gingivalis -associated mediators of systemic inflammation (such as CRP, IL-6, TNF-α), contributing to both endothelial dysfunction and the development of arterial hypertension [ 61 ]. Recently, an animal study supported the hypothesis that the Th1 immune response induced by P. gingivalis antigens is response for elevated BP [ 60 ].…”
Section: Cardiologymentioning
confidence: 99%
“…Locally produced GM-CSF activates sensory neurons expressing the GM-CSF receptor, transmitting painful stimuli to ascending nociceptive pathways in the spinal cord and brain [76,77]. Viafara-García et al reported that P. gingivalis or Pg-LPS treatment induced GM-CSF and angiotensin II production in coronary artery endothelial cells [78]. There might be a possibility that continual P. gingivalis influx from the oral cavity into the gut might be associated with patient pain due to increased GM-CSF levels.…”
Section: Discussionmentioning
confidence: 99%
“…75 Etiologically, P. gingivalis could invade vascular endothelial cells and enhance pro-inflammatory chemokine production, and endothelial cell dysfunction promoted immune cell infiltration. 76 In physiological conditions, endothelial cells manufacture protective molecule NO, which enhances artery dilation and inhibits leukocyte adhesion. However, P. gingivalis-released OMVs suppressed the activity of endothelial nitric oxide synthase (eNOS), a speed-limiting enzyme for NO synthesis, and thus contributed to the development of atherosclerosis.…”
Section: Atherosclerosismentioning
confidence: 99%